2017
DOI: 10.1001/jamaoto.2016.4056
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Otolaryngology Consultation Patterns at an Academic Quaternary Care Center

Abstract: The consultation volume of an otolaryngology-head and neck surgery service requires significant time and resources. Consultations are most often for rhinologic or laryngologic issues and are reflective of the clinical setting in which the patient is evaluated. Cost savings may be realized by increasing health care access points for nonurgent concerns that can be evaluated in an outpatient setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 21 publications
3
33
0
2
Order By: Relevance
“…Emergent ORL-HNS disorders are sensitive and acute and require many consultations for the patients to receive appropriate point-of-care service and follow-up [ 11 ]. We selected the 10 most common emergent ORL-HNS disorders, including foreign body, epistaxis, ear trauma, acute otitis externa, deep neck infection, head and neck cancer and associated complications, acute otitis media, nasal trauma, acute pharyngotonsillitis, and sudden deafness (in descending order based on consultation frequency) among 300 consecutive patients who visited an otolaryngologist in 2004 at our Department of Emergency.…”
Section: Methodsmentioning
confidence: 99%
“…Emergent ORL-HNS disorders are sensitive and acute and require many consultations for the patients to receive appropriate point-of-care service and follow-up [ 11 ]. We selected the 10 most common emergent ORL-HNS disorders, including foreign body, epistaxis, ear trauma, acute otitis externa, deep neck infection, head and neck cancer and associated complications, acute otitis media, nasal trauma, acute pharyngotonsillitis, and sudden deafness (in descending order based on consultation frequency) among 300 consecutive patients who visited an otolaryngologist in 2004 at our Department of Emergency.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have reported a high frequency of these pathologies in children, 52.72% of children received urgently in the ENT-CFS department of Yopougon University Hospital in Ivory Coast [4] and 11.23% in Antananarivo in Madagascar [5]. Otherwise, pediatric ENT consultations accounted for 26.8% of all ENT-CFS consultations at Duke University Medical Center in North Carolina in the United States [6], and 21% of children under 10 years old. 15 years were received in outpatient ENT consultation at the Clinical Hospital of the University of Chile, Chile [7].…”
Section: Introductionmentioning
confidence: 99%
“…The few studies previously addressing this in our country have looked at consult volume seen over a short time period (1 year) as well as the most common consults seen. 7,8 One previous study has examined otolaryngology consult volume trends outside of the United States and found a 120% increase in consult volume over a 5 year time period within a five hospital health region. 9 In this study, we investigate how the volume of otolaryngology consults has changed over a 4-year time period at a single institution in the United States and specifically examine trends based on the location and time of the consultations.…”
mentioning
confidence: 99%